The temporal dimension of business processes - dealing with time constraints - Pereira, José Luís (2017)
The execution of business processes has a temporal dimension and many times there is a set of time constraints that processes have to comply with. Unfortunately, both in terms of process modeling languages as well as systems used to manage business processes, the support for the time dimension is still very poor. In this paper, we describe the main time constraints that need to be considered in the management of business processes and process modeling languages need to incorporate. Furthermore, we point out some avenues for future research.